1997
DOI: 10.1212/wnl.48.4.985
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E ϵ4 allele and hippocampal volume in twins with normal cognition

Abstract: We examined the relation of APOE-epsilon 4, hippocampal volume, and cognitive performance in ten pairs of cognitively normal twins who had a mean age of 62.5 years (SD = 7.8). There were no significant differences in neuropsychological measures of the groups categorized by the presence of an epsilon 4 allele. However, the mean normalized right and left hippocampal volumes were smaller in the epsilon 4 groups compared to the group without epsilon 4. Combined with prior reports, these findings suggest that epsil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
92
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(102 citation statements)
references
References 0 publications
9
92
1
Order By: Relevance
“…These observations are important since previous work, including our own, has suggested that APOE may affect normal neurocognitive performance in aging in addition to being a risk factor for AD (e.g. Plassman et al, 1997;Reed et al, 1994). The current findings suggest that differences on memory measures may reflect very early, undetected disease rather than "normal" cognitive variability related to the different APOE polymorphisms (Smith et al, 1998;Bondi et al, 1999).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…These observations are important since previous work, including our own, has suggested that APOE may affect normal neurocognitive performance in aging in addition to being a risk factor for AD (e.g. Plassman et al, 1997;Reed et al, 1994). The current findings suggest that differences on memory measures may reflect very early, undetected disease rather than "normal" cognitive variability related to the different APOE polymorphisms (Smith et al, 1998;Bondi et al, 1999).…”
Section: Discussionsupporting
confidence: 55%
“…Some studies have shown lower cognitive function in non-demented individuals carrying one or more APOE ε4 alleles (e.g. Reed et al, 1994;Plassman et al, 1997;Caselli et al, 2004); whereas, others have suggested that group differences are related to the early AD phenotype and are not a function of normal cognitive aging (Smith et al, 1998). Data from the Cache County Study suggest that APOE genotype may play a role in the "timing" of AD onset (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These early "preclinical" memory changes are more likely to occur in those with a genetic susceptibility marker for AD, the apolipoprotein E (APOE) ε4 allele [11,37], than in those without this risk factor. In parallel with these findings, structural [32,44] and functional [4,6,15,20,34,42] neuroimaging alterations are more evident in non-demented elderly with the ε4 allele than in those without this allele type.…”
Section: Introductionmentioning
confidence: 52%
“…Previous reports concerning effects of APOE 4 on hippocampal atrophy from cross-sectional MRI are quite variable [23,33,39,45]. The longitudinal MRI study by Cohen et al showed that atrophy rate of hippocampus was higher in CN subjects with APOE 4 than those without APOE 4 [6].…”
Section: Discussionmentioning
confidence: 98%